COMPLEX FRACTURES OF THE DISTAL RADIUS: ANALYSIS OF OSTEOSYNTHESIS USING SPANNING PLATES - TÚLIO FELÍCIO DA CUNHA RODRIGUES; AFRÂNIO DONATO DE FREITAS; JOÃO ANTONIO CÔRTES VIEIRA; JUAN CAMILO ORTEGA RIVERA; RODRIGO MITRE COTTA (Acta Ortopédica Brasileira)
ABSTRACT Objective: To radiographically evaluate the postoperative results of AO 2R3C3 type distal radius fractures treated using the spanning plate technique, associated or not with other fixation methods. Methods: Retrospective observational study that evaluated 14 patients, aged 29 to 80 years, who underwent osteosynthesis, from November 2021 to June 2022. For radiographic measurement, the following parameters were defined: ulnar variance, volar inclination, radial inclination and step articulate. Results: The mean value of radial inclination was 13.70 degrees, volar inclination was 0.85 degrees, ulnar variance was 0.60mm and joint step was 0.78mm. Conclusion: Fixation using spanning plate is an excellent alternative in the management of complex fractures of the distal radius. Level of Evidence IV, Case Series.